2019
DOI: 10.1136/bmjopen-2019-032021
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences between those doctors who apply for a training post in Foundation Year 2 and those who take time out of the training pathway? A UK multicohort study

Abstract: IntroductionKnowledge about the career decisions of doctors in relation to specialty (residency) training is essential in terms of UK workforce planning. However, little is known about which doctors elect to progress directly from Foundation Year 2 (F2) into core/specialty/general practice training and those who instead opt for an alternative next career step.ObjectiveTo identify if there were any individual differences between these two groups of doctors.DesignThis was a longitudinal, cohort study of ‘home’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…In the UK, students and junior doctors take time off for various reasons including further application enhancement for specialty (residency) training or a career break to achieve life goals. 3,4 All of which may enhance emotional intelligence composites stated in this study, such as self-actualization and empathy.…”
Section: Dear Editormentioning
confidence: 82%
“…In the UK, students and junior doctors take time off for various reasons including further application enhancement for specialty (residency) training or a career break to achieve life goals. 3,4 All of which may enhance emotional intelligence composites stated in this study, such as self-actualization and empathy.…”
Section: Dear Editormentioning
confidence: 82%
“…The central importance of trainee doctors feeling over-worked and under-valued has been raised before in previous work, predominantly from questionnaire surveys (8,9,(12)(13)(14), and is a widespread concern across the NHS workforce (16). Similarly, a need for more support for Foundation doctors has been recently highlighted by other authors (17).…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…The central importance of trainee doctors feeling over-worked and under-valued has been raised before in previous work, predominantly from questionnaire surveys (8,9,(12)(13)(14) (8,9,(12)(13)(14), and is a widespread concern across the NHS workforce (15). Similarly, a need for more support for Foundation doctors has been recently highlighted by other authors (16).…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…A novel discrete choice experiment studied revealed that trainees place most value in their training post on good working conditions, good opportunities for their partners and desirable geographical location (8). More recent work has suggested some differences in socioeconomic status between trainees who do and do not take time out of the training pathway (9). A lack of flexibility may also be key with some experts describing the current system as "an inflexible training pipeline" (10).…”
Section: Introductionmentioning
confidence: 99%